Pre-Design of Infographic Based on The Structure And Mechanism of Virus Infection at Elementary School Levels in Ternate City - Said Hasan; Abdu Mas’ud; Ade Haerullah; Sundari Sundari (Journal of Biology Learning, 2022)
During the COVID-19 pandemic and the new normal, teacher innovation is urgently needed to make their students not bored and stressed in the learning process, either virtual or face-to-face. In North Maluku, face-to-face learning has been carried out with simulations and strict protocols. Learning variations using Blended Learning become a general solution that is applied. Infographics are information graphics which are visual representations of a collection of data, information and designs. Infographics require a large amount of information in the form of writing or numbers and then converted into a simpler form, namely a combination of images and text that allows readers to quickly understand the meaning of a message or image itself. Various efforts to educate covid 19 both non-formally and formally have been carried out to prevent infection, social restrictions and the provision of social and medical assistance have been carried out by the government, but the public still does not have good awareness and discipline towards covid 19. This study aims to educate about the virus and its dangers, especially covid 19 through the development of infographic-based science teaching aids in elementary schools. Research Development with reference to 4D models with modifications. The results of the study indicate that infographic media is suitable for use as media material or science teaching aids, especially virus education for elementary school students. The use of infographics related to viruses and infection mechanisms can be used in various ways in online and offline learning for elementary school students